Micro- and nanoscale characterization of different natural biomaterials for ocular surface regeneration - Dereli Can, Gamze; Tevlek, Atakan; Can, Mehmet Erol; Öncü, Elif; Aydın, Halil Murat; Cagil, Nurullah (The European Research Journal, 2020)
Objectives: This study aims to characterize the widely used biological derived membranes in clinics in terms of micro-nano scale mechanical and morphological properties. Within this scope, advanced platelet-rich fibrin (A-PRF), leucocyte-and platelet-rich fibrin (L-PRF) and human amniotic membrane were studied in this research study. Methods: Nano-indentation, optical coherence tomography (OCT), scanning electron microscopy (SEM), and in vitro degradation test were performed for material characterization. Results: The nano-indentation test revealed significantly higher modulus of elasticity and hardness values in A-PRF group, while OCT presented significantly higher thickness measurements when compared L-PRF. A loose 3D architecture formation due to the large pores formed by means of large fiber diameter were observed in A-PRF group. Besides, platelets were observed among the large fibers in A-PRF membranes on the contrary of L-PRF membranes. Low fiber diameter and high cellular separation were recorded in L-PRF group due to the high centrifugal force application. Therefore, it was observed that the platelets were located mostly on the surface of the membranes in L-PRF. The loose 3D architecture of A-PRF membranes is thought to release growth factors for a longer period of time, ensuring cellular integrity. On the other hand, degradation test results indicated that amniotic membranes degrade to about 85% in one week, while L-PRF and A-PRF were lost their initial weights approximately 31% and 40%, respectively. Conclusions: This comparative characterization study of three different natural biomaterials used in a wide range of clinical applications, from dentistry to ophthalmology, was thought to guide surgeons on the selection of site-specific material.